2022
DOI: 10.3390/biomedicines10050968
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Valproic Acid on SLC12A2, SLC12A5 and SLC5A8 Gene Expression in Pediatric Glioblastoma Cells as an Approach to Personalised Therapy

Abstract: Valproic acid (VPA) is a histone deacetylase inhibitor with sex-specific immunomodulatory and anticancer effects. This study aimed to investigate the effect of 0.5 and 0.75 mM VPA on NKCC1 (SLC12A2), KCC2 (SLC12A5) and SLC5A8 (SLC5A8) co-transporter gene expressions in pediatric PBT24 (boy’s) and SF8628 (girl’s) glioblastoma cells. The SLC12A2, SLC12A5 and SLC5A8 RNA expressions were determined by the RT-PCR method. The SLC12A2 and SLC5A8 expressions did not differ between the PBT24 and SF8628 controls. The SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Slc5a8 expression can be upregulated by DNA demethylation. VPA can induce the effect on Slc5c8 gene expression upregulation via DNA demethylation in cancer cells [ 81 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Slc5a8 expression can be upregulated by DNA demethylation. VPA can induce the effect on Slc5c8 gene expression upregulation via DNA demethylation in cancer cells [ 81 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently the different temozolomide and valproic acid effects on tumorigenesis mechanisms have been reported, such as their effect on tumor growth, the histological expression of PCNA and EZH2 in tumor cells, Na-K-2Cl, K-Cl, and SLC5A8 co-transporter gene expression in pediatric glioblastoma PBT24 and SF8628 cell tumors on chick embryo chorioallantoic membranes (CAM) and on corresponding cells in vitro, highlighting the importance of studies on efficacy in the context of individualized anticancer therapy [ 37 , 38 ]. This study’s novelty lies in the differential effect of the active substance DCA‘s anions on PBT24 and SF8628 tumors on the CAM and the cells in vitro, comparing the differences in the impact of the studied NaDCA and MgDCA salts.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with a combination of VPA and dichloroacetate significantly increased Slc5a8 gene expression and showed a significant anti-inflammatory effect on thymocytes from male mice [19], and treatment of T lymphocytes from males and females with this combination showed a significant anti-inflammatory effect and gender-related differences [20]. It was reported that different VPA effect the expression of the SLC12A2 (NKCC1) and SLC12A5 (KCC2) co-transporter genes in pediatric glioblastoma PBT24 (boys) and SF8628 (girls) cells [21]. The molecular and clinical role of cation-chloride co-transporters illustrates the significant association of KCC2 and NKCC1 with tumorigenesis.…”
Section: Introductionmentioning
confidence: 96%
“…VPA-treated GBM cells secreted high amphiregulin levels, whose expression was positively correlated with resistance to TMZ of different GBM cells [23]. VPA induces the activation of the Na + -K + -2Cl -co-transporter (NKCC1), significantly increasing the expression of the NKCC1 gene (SLC12A2) in PBT24 but not affecting SF8628 cells [21]. The TMZ caused significantly increased RNA expression of the SLC12A2 in both PBT24 and SF8628 cell types [24].…”
Section: Introductionmentioning
confidence: 99%